Assessment of National Open University of Nigeria (NOUN) Students' Use of Computers for Electronic Examination in South-west, Nigeria - Adebanjo, Adetayo Adekunle (West African Journal of Open and Flexible Learning, 2021)
This study assessed students' use of computer for electronic examination in the National Open University of Nigeria (NOUN). Simple random sampling techniques was employed to draw a sample size of nine hundred (900) distance learners from 100 and 200 levels respectively in Ogun, Ekiti and Oyo State NOUN study centres. Data collection was done by means of a structured questionnaire which was subjected for face and content validating using Cronbach's alpha test. The results yielded reliability coefficient of 0.76 and above. The data collected were analysed using frequency counts, percentage distribution, means, standard deviations and students t-test. The result showed significant difference in online computer use between male and female students, and that there was significant difference in NOUN students' on the use of computer for electronic examination based on their faculties (Law, Education, Management Sciences, Science and Technology and Arts and Social Sciences). The study therefore recommended that all students of NOUN should be encouraged to procure mobile technologies such laptops, Ipad, internet enabled mobile phones compulsorily for easy access and effective preparation for e-exams. Intensive seminars, trainings and workshops should be organised for students on how to harmonize the use digital technologies for improved performance via eexamination platforms. Abstrait Cette étude a évalué l'utilisation de l'ordinateur par les étudiants pour l'examen électronique à National Open University of Nigeria (NOUN). Des techniques d'échantillonnage aléatoire simples ont été utilisées pour tirer un échantillon de neuf cents (900) apprenants à distance des 1er et 2eme niveaux respectivement dans les centres d'étude NOUN d'Ogun, d'Ekiti et d'Oyo. La collecte des données a été effectuée au moyen d'un questionnaire structuré qui a été soumis pour validation du visage et du contenu à l'aide du test alpha de Cronbach. Les résultats ont donné un coefficient de fiabilité de 0,76 et plus. Les données recueillies ont été analysées à l'aide des comptages de fréquence, de la distribution en pourcentage, des moyennes, des écarts-types et du test t d'étudiants. Le résultat a montré une différence significative dans l'utilisation de l'ordinateur en ligne entre les étudiants masculins et féminins, et qu'il y avait une différence significative dans l'utilisation de l'ordinateur par les étudiants de NOUN pour les examens électroniques en fonction de leurs facultés (Droit, éducation, sciences de Gestion, Sciences et Technologie et Arts et Sciences Sociales). L'étude a donc recommandé que tous les étudiants de NOUN soient encouragés à se procurer obligatoirement des technologies mobiles telles que des ordinateurs portables, des Ipad, des téléphones mobiles compatibles Internet pour un accès facile et une préparation efficace aux examens électroniques. Des séminaires intensifs, des formations et des ateliers devraient être organisés pour les étudiants sur la manière d'harmoniser l'utilisation des technologies numériques pour améliorer les performances via les plateformes d'examen en ligne.